GIN W BUTELCE LEJDEJSKIEJ. NIDERLANDZKIE POŻYCZKI JĘZYKOWE W POLSZCZYŹNIE I ICH POLA SEMANTYCZNE - Kowalska-Szubert, Agata (Scripta Neophilologica Posnaniensia, 2019)
The goal of this paper is to familiarize Polish readers with the Dutch borrowings functioning in modern Polish as well as the semantic fields which those borrowings belong to. Moreover, the authorasks the question of whether the criteria of classifying the origin of foreign lexemes applied by Polish lexicographers are clear, consistent and whether those criteria encompass all possible options.